Whole genome sequencing of marine organisms by Oxford Nanopore Technologies: Assessment and optimization of HMW‐DNA extraction protocols - Sonia Boughattas (508422) (2021)
Marine habitats are Earth's largest aquatic ecosystems, yet little is known about marine organism's genomes. Molecular studies can unravel their genetics print, thus shedding light on specie's adaptation and speciation with precise authentication. However, extracting high molecular weight DNA from marine organisms and subsequent DNA library preparation for whole genome sequencing is challenging. The challenges can be explained by excessive metabolites secretion that co‐precipitates with DNA and barricades their sequencing. In this work, we sought to resolve this issue by describing an optimized isolation method and comparing its performance with the most commonly reported protocols or commercial kits: SDS/phenol–chloroform method, Qiagen Genomic Tips kit, Qiagen DNeasy Plant mini kit, a modified protocol of Qiagen DNeasy Plant kit, Qiagen DNeasy Blood and Tissue kit, and Qiagen Qiamp DNA Stool mini kit. Our method proved to work significantly better for different marine species regardless of their shape, consistency, and sample preservation, improving Oxford Nanopore Technologies sequencing yield by 39 folds for Spirobranchus sp. and enabling generation of almost 10 GB data per flow cell/run for Chrysaora sp. and Palaemon sp. samples. Other Information Published in: Ecology and Evolution License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ece3.8447